EVALUASI PROGRAM SERTIFIKASI MANAJEMEN RISIKO BAGI PENGURUS DAN PEJABAT BANK UMUM (Studi Pada Bank-Bank Umum di Wilayah Jakarta, Bandung, Semarang, dan Surabaya) - GUNHERANI, DEWI (Jurnal Ilmiah Educational Management, 2015)
The objective of this research is to evaluate the risk management certification program for the administrator and officer of comercial bank in Jakarta, Bandung, Semarang and Surabaya Area. The evaluation focused on urgency, design, planning, implementation, outcome and impact of risk management certification program. Qualitative approach used in this research with program evaluation design. Program evaluation used in this researh is discrepansy model. Data collecting in-depth interview, orbservation and docemantation study. Interview conducted with administrator and official of commercial bank as a key informant. Data analyzed quantitatively stage, that is data reduction, data display, and conclussion drawing. Based on the findings, then be concluded that aspect of generally urgency, design, planning, implementation, outcome and impact of risk management certification program meet or in accordance with the criteria that established to evaluted risk management certification program. Only aspect evaluation and supervisory from the central bank of the Republic of Indonesia as program owner that not in accordance with the criteria. Therefore, risk management certification program must be continued and take improving on evaluation and supervisory aspects.